The relationship between EFL teachers' reflective thinking and their teaching style in Iranian EFL context. Issue 5 (3rd September 2022) - Abdar, Sayeh; Shafaei, Ali
ABSTRACT: Reflective thinking and teaching style are considered as two prominent and influential factors in the process of education. There have been several studies carried out to investigate different aspects of each of these two factors. However, no studies have been done to explore the possible relationship between these two crucial elements. Therefore, the present study set out to fill the gap and explore the relationship between reflective thinking and teaching style among EFL teachers in Iran. Ninety EFL teachers including 50 males and 40 females were chosen as the participants of this research. The questionnaires selected for the data collection phase were given to the teachers and they were asked to fill them out. The collected data were analyzed and it was found that there was a positive correlation between EFL teachers' reflective thinking and their teaching style. The results of this research study can be of use for EFL teachers and teacher educators.